Edukasi Pemanfaatan Potensi Daun Kelor Sebagai Upaya Pencegahan Stunting Pada Masyarakat Desa Powelua Kabupaten Donggala Sulawesi Tengah - Muthmainah Tuldjanah; Erick Budiawan; Sasdila; Putri Natalia; Leligrafela Tudaan (LPPM Universitas Al Muslim, 2024)
Stunting is a disorder where the growth and development of toddlers is hampered due to malnutrition during pregnancy and this condition is known by looking at the child's body condition which is smaller than other children of the same age. Overcoming stunting is one of the programs of the Donggala Regency Government because of the large number of stunted children in the district, one of which is Powelua Village. Many factors can cause delays in the growth and development of toddlers, including toddler characteristics and socio-economic factors. The number of families at risk of stunting in Powelua Village in 2023 reached 58 children with a total of 150 Heads of Families. This community service activity aimed to educate the public that Moringa leaves have a very high nutritional content, especially their potential in preventing stunting. One way to prevent stunting is to provide education related to the potential use of Moringa leaves in preventing stunting which wass delivered in the form of lectures with material, as well in the form of leaflets, followed by a questions-and-answers session. Evaluation of achievement was carried out by providing pre-tests and post-tests to the community on the material presented with a success indicator of 74.27% of parents understanding the education provided. The results of implementing this community service activity showed an increase in knowledge of 88.67% with a very good category.